Crowdfunding as an alternative for developing investigative journalism: a baseline analysis of the education sector in Portugal - Dos Santos, Maria José Palma Lampreia (2020)
The subprime crisis from 2007 and the availability of free news on the Internet led to a drastic decrease of investigative journalism in Portugal. Crowdfunding could be an alternative to traditional models of financing investigative journalism. The present paper aims to analyze the crowdfunding for financing investigative journalism in that country. The methodology used is exploratory. The main results highlight confirm the low entrepreneurial skills of journalists. We suggest the future inclusion of courses in economics and entrepreneurship in the academic degrees in Portugal to overcome this problem.